Exploring the Historical Significance of the Social Security and Welfare Systems in Islam: The Era of ’Umar ibn al-Khattab - Nadvi, Muhammad Junaid; Khalid, Mohammad (Journal of Al-Tamaddun, 2023)
Islam’s social security system differs in nature and operation from the social security systems that are widely used around the world. The Muslim world has had access to a commendable social security system from the beginning of Islam, therefore modern social security systems are nothing new to them. In this article, the Islamic social security system under the rule of ’Umar ibn al-Khattb, the second khalifah of Islam, is studied historically.